2017
DOI: 10.1158/0008-5472.can-16-2797
|View full text |Cite
|
Sign up to set email alerts
|

TWIST1-WDR5-Hottip Regulates Hoxa9 Chromatin to Facilitate Prostate Cancer Metastasis

Abstract: TWIST1 is a transcription factor critical for development which can promote prostate cancer metastasis. During embryonic development, TWIST1 and HOXA9 are co-expressed in mouse prostate and then silenced post-natally. Here we report that TWIST1 and HOXA9 co-expression are re-activated in mouse and human primary prostate tumors and are further enriched in human metastases, correlating with survival. TWIST1 formed a complex with WDR5 and the lncRNA Hottip/HOTTIP, members of the MLL/COMPASS-like H3K4 methylases, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 48 publications
2
85
0
2
Order By: Relevance
“…To elucidate their significance in ESCC, it is necessary to clarify the association between their expression patterns and patient prognosis. It was shown that the survival time of patients with high HOXB7 or HOXC6 or HOXC8 expression was significantly shorter than that of patients with low expression, which is similar to the results of other groups . As reported, the consequences of dysregulated HOX genes in carcinogenesis can be interpreted as an extension of their normal function .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…To elucidate their significance in ESCC, it is necessary to clarify the association between their expression patterns and patient prognosis. It was shown that the survival time of patients with high HOXB7 or HOXC6 or HOXC8 expression was significantly shorter than that of patients with low expression, which is similar to the results of other groups . As reported, the consequences of dysregulated HOX genes in carcinogenesis can be interpreted as an extension of their normal function .…”
Section: Discussionsupporting
confidence: 86%
“…It was shown that the survival time of patients with high HOXB7 or HOXC6 or HOXC8 expression was significantly shorter than that of patients with low expression, which is similar to the results of other groups. [27][28][29] As reported, the consequences of dysregulated HOX genes in carcinogenesis can be interpreted as an extension of their normal function. [30][31][32] Given that HOX genes can be viewed as global regulators of growth and differentiation, we investigated whether they could modulate the malignant phenotype in es- Consequently, it becomes difficult to interpret these data and determine the exact contribution of any of these individual genes to a malignant phenotype.…”
Section: Discussionmentioning
confidence: 86%
“…Increasing evidence indicates that HOTTIP is overexpressed in prostate cancer, lung cancer, and pancreatic cancer . HOTTIP knockdown impedes cell viability, proliferation, invasion, and angiogenesis in human cancer cells, therefore it is been identified as an oncogenic long noncoding RNA (lncRNA).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal looping of this locus brings the HOXA genes into close proximity to HOTTIP , which activates the expression of the predominantly 5′ located HOXA genes. Interestingly, the deregulation of HOXA genes by HOTTIP has been implicated in the development and progression of prostate cancer, as well as in the clinical disease progression of hepatocellular carcinoma patients . Mechanistically, HOTTIP has been suggested to specifically interact with the lysine methyltransferase complex WDR5‐MLL to facilitate histone 3 lysine 4 trimethylation (H3K4me3) and hence transcriptional activation of this locus .…”
Section: Gene Regulatory Functions Of Lncrna Loci In the Nucleusmentioning
confidence: 99%
“…Interestingly, the deregulation of HOXA genes by HOTTIP has been implicated in the development and progression of prostate cancer, as well as in the clinical disease progression of hepatocellular carcinoma patients. 25,26 Mechanistically, HOTTIP has been suggested to specifically interact with the lysine methyltransferase complex WDR5-MLL to facilitate histone 3 lysine 4 trimethylation (H3K4me3) and hence transcriptional activation of this locus. 24,27 However, the specificity and in vivo relevance of this RNA-protein interaction is still unclear because all of the studies conducted so far comprise either in vitro RNA pulldown or native RNA immunoprecipitation experiments, which are both known to be prone to return falsepositive RNA-protein interactions.…”
Section: Gene Regulatory Functions Of Lncrna Loci In the Nucleusmentioning
confidence: 99%